Evaluation the resolution of : [GPR radargram] influenced by [LNAPL] based different type of frequency / Abdullah Hadi Shabri - Shabri, Abdullah Hadi (2018)
The contaminated o f subsoil usually happens because o f the leakage of hydrocarbon from buried tanks or pipe. Hydrocarbons usually come in the form of liquids and gaseous with different saturation. These hydrocarbons will interfere with electromagnetic wave from GPR and give an effect to GPR data. The purpose of this paper is to determine the resolution o f GPR radargram based on different frequeny. Objectives of this study are to evaluate the vertical and horizontal resolution o f GPR radargram based on different antenna frequency for clean and contaminated soil and to analyse the accuracy of GPR resolution for high and low frequency. The experiment were conducted using dual antennae ground penetrating radar (GPR) systems with frequency of 250 MHz and 800 MHz were deploy. As a prelude to acquisition o f field data, a simulation o f GPR surveys was held on a site in UiTM Aran, Perlis. A pvc pipe was planted in 3 different soil which are fine sand, coarse sand and gravel. The depth of the pipe was approximately 0.5m from the surface o f soil. GPR survey were done on the original soil condition and then a new GPR scanning were conducted after the soil had been contaminated by diesel. Next the GPR data being process and filter by using REFLEXW software to get the necessary parameter to calculate and analyze the resolution o f radargram. The output o f this study shows that the influence o f diesel in soil give a rise in relative permittivity o f media and thus affected the horizontal and vertical resolution.